Machine-learning-based contrast-enhanced computed tomography radiomic analysis for categorization of ovarian tumors - Li, Jiaojiao; Zhang, Tianzhu; Ma, Juanwei; Zhang, Ningnannan; Zhang, Zhang; Ye, Zhaoxiang (Frontiers in Oncology, 2022)
Objectives To evaluate the diagnostic performance of machine learning-based contrast-enhanced CT radiomic analysis for categorizing benign and malignant ovarian tumors. Methods A total of 1329 patients with ovarian tumors were randomly divided into a training cohort (N=930) and a validation cohort (N=399). All tumors were resected and pathological findings were confirmed. Radiomic features were extracted from the portal venous phase images of contrast-enhanced CT. The clinical predictors included age, CA-125, HE-4, ascites, and margin of tumor. Both radiomics model (including selected radiomic features) and mixed model (incorporating selected radiomic features and clinical predictors) were constructed respectively. Six classifiers [k-nearest neighbor (KNN), support vector machines (SVM), random forest (RF), logistic regression (LR), multi-layer perceptron (MLP) and eXtreme Gradient Boosting (XGBoost)] were used for each model. The mean relative standard deviation (RSD) and area under the receiver operating characteristic curve (AUC) were applied to evaluate and select the best classifiers. Then, the performances of the two models with selected classifiers were assessed in the validation cohort. Results The MLP classifier with the least RSD (1.21 and 0.53 respectively) was selected as the best classifier in both radiomics and mixed models. The two models with MLP classifier performed well in the validation cohort, with the AUCs of 0.91 and 0.96, with accuracies (ACCs) of 0.83 and 0.87, respectively. The Delong test showed that the AUC of mixed model was statistically different from that of radiomics model (p<0.001). Conclusions Machine learning-based CT radiomic analysis could categorize ovarian tumors with good performance preoperatively. The mixed model with MLP classifier may be a potential tool in clinical applications.